2002
DOI: 10.1677/joe.0.1740195
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of rat Sertoli cell function by FSH: possible role of phosphatidylinositol 3-kinase/protein kinase B pathway

Abstract: The FSH molecular mechanism of action is best recognized for its stimulation of the adenylyl cyclase/cAMP pathway via activation of a G protein. Recently, links between cAMP, phosphatidylinositol 3-kinase (PI3K) and protein kinase B (PKB) signaling pathways in thyroid and granulosa cells have been observed. The aim of this study was to investigate the possible role of the PI3K/PKB pathway in FSH regulation of Sertoli cell function. Twenty-day-old rat Sertoli cell cultures were used. An increase in phosphorylat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
63
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 103 publications
(66 citation statements)
references
References 54 publications
3
63
0
Order By: Relevance
“…In other cell types various results have been obtained. In cardiomyocytes [37], isoproterenol-induced phosphorylation of PKB was PKA and PI3K dependent, whereas, in COS cells [19], cAMP-induced PKB activation was PKA-dependent but PI3K-independent, and in Sertoli cells [39], dbcAMP-induced activation of PKB was PKAindependent but PI3K-dependent. These data strengthen the hypothesis about the specificity of certain signalling events with regard to different tissues.…”
Section: Discussionmentioning
confidence: 96%
“…In other cell types various results have been obtained. In cardiomyocytes [37], isoproterenol-induced phosphorylation of PKB was PKA and PI3K dependent, whereas, in COS cells [19], cAMP-induced PKB activation was PKA-dependent but PI3K-independent, and in Sertoli cells [39], dbcAMP-induced activation of PKB was PKAindependent but PI3K-dependent. These data strengthen the hypothesis about the specificity of certain signalling events with regard to different tissues.…”
Section: Discussionmentioning
confidence: 96%
“…cAMP modulates Akt in different cell types, including fibroblasts (33,34,45,63), hepatocytes (42), adipocytes (41,64), cardiomyocytes (40), skeletal muscle (43), neurons (48), Schwann (39), endothelial (46), and endocrine cells (38,65). Specifically, in thyroid cells, the role of Akt in TSH-mediated proliferation of nontransformed cells is still controversial; either no effects (66) or both positive (67-69) and negative (47) effects of TSH on Akt phosphorylation/activity have been reported.…”
Section: Discussionmentioning
confidence: 99%
“…cAMP can either stimulate (33)(34)(35)(36)(37)(38)(39)(40)(41)(42)(43) or inhibit (44 -50) Akt activity. We have previously reported that cAMP inhibited Akt activity in PCCL3 thyroid cells via the GTP-binding protein Rap1b (47) and suggested that it played a role in TSH mitogenic action in these cells.…”
mentioning
confidence: 99%
“…Interestingly, there is accumulating evidence that the PI3K/PKB pathway plays an important role in the formation and stabilization of AJs, linking AJ components to the cytoskeleton in keratinocytes, intestinal epithelial cells, mammary epithelial cells, and Caco-2/15 cells (18,19). In the testis, PI-4,5-P 2 and phosphoinositide-specific phospholipase C have been identified in the ES (20), and the PI3K/PKB signaling pathway has recently been shown to be regulated by follicle-stimulating hormone in 20-day-old Sertoli cells (21)(22)(23). However, little is known regarding the upstream and downstream mediators of the PI3K/PKB signaling pathway in the testis and its contribution to junction dynamics, especially at the apical ES.…”
mentioning
confidence: 99%